The optimum overlay thickness of prefabricated full-depth precast concrete bridge deck panel system – 3D non-linear finite element modeling. (1st October 2015) - Al-Rousan, Rajai Z.; Alhassan, Mohammad; Issa, Mohsen A.
Highlights: Protective overlays with high performance are vital for segmental bridge system. Overlay thickness of 38–63 mm is the optimum thickness. The overlay thickness increasing had a strong impact on the bond strength. Abstract: Segmental construction of prefabricated full-depth concrete bridge deck systems results in numerous transverse and longitudinal joints as well as shear connector pockets that receive cast-in-place concrete or grout. In such systems, it is necessary to overlay the bridge deck to provide smooth riding surface and to protect the underlying deck reinforcement from the deicing salts-induced corrosion and consequent spalling and delamination of the concrete. This paper reports on results and findings obtained from a non-linear finite element analysis (NLFEA) of a prototype prefabricated full-depth precast concrete bridge deck panel system before and after being overlaid with various plain and fibrous latex-modified concrete (LMC) and microsilica concrete (MSC) overlays. The NLFEA were validated with experimental results obtained from full-scale testing of the prototype bridge system. The benefits of the NLFEA can be highly appreciated when visualizing the substantial time and cost savings, the ability to change any parameter of interest, and the capability of demonstrating any interesting response at any load value and at any location in the system. The most attractive results were: (1) adequately bonded LMC or MSC overlay significantly improves the stiffness, cracking load, and ultimate strength capacity of the system, (2) AASHTO HS20 truck induced bond stresses were below the bond strength of bonded LMC and MSC overlays, (3) the fibrous overlay has desirable crack arresting characteristic.